2015
DOI: 10.1128/jvi.01881-15
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of the R263K and T66I Resistance Substitutions in HIV-1 Integrase Is Incompatible with High-Level Viral Replication and the Development of High-Level Drug Resistance

Abstract: The R263K substitution in integrase has been selected in tissue culture with dolutegravir (DTG) and has been reported for several treatment-experienced individuals receiving DTG as part of salvage therapy. The R263K substitution seems to be incompatible with the presence of common resistance mutations associated with raltegravir (RAL), a different integrase strand transfer inhibitor (INSTI). T66I is a substitution that is common in individuals who have developed resistance against a different INSTI termed elvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…While the latter had no effects on resistance to DTG, the addition of H51Y to R263K increased resistance to DTG to ϳ8-fold, while dramatically decreasing viral replication capacity by ϳ90% and enzyme strand transfer activity by ϳ80% (Mesplède et al 2013). Other studies have shown that R263K in combination with M50I, G118R, H51Y, E138K, T66I, N155H, or M184I/V slightly increased resistance to DTG but did not restore viral replication capacity (Quashie et al 2013aWares et al 2014;Anstett et al 2015;Liang et al 2015). Interestingly, no additional compensatory mutations have been identified for DTG, even in cell culture selection experiments conducted over more than 4 years (Wainberg and Han 2015).…”
Section: >100 Nd <50mentioning
confidence: 99%
“…While the latter had no effects on resistance to DTG, the addition of H51Y to R263K increased resistance to DTG to ϳ8-fold, while dramatically decreasing viral replication capacity by ϳ90% and enzyme strand transfer activity by ϳ80% (Mesplède et al 2013). Other studies have shown that R263K in combination with M50I, G118R, H51Y, E138K, T66I, N155H, or M184I/V slightly increased resistance to DTG but did not restore viral replication capacity (Quashie et al 2013aWares et al 2014;Anstett et al 2015;Liang et al 2015). Interestingly, no additional compensatory mutations have been identified for DTG, even in cell culture selection experiments conducted over more than 4 years (Wainberg and Han 2015).…”
Section: >100 Nd <50mentioning
confidence: 99%
“…The study of Liang et al showed that the T66I substitution emerged from a wild-type virus but also from a R263K mutant and from a E138K-R263K double-mutant virus under RAL or EVG pressure [ 17 ]. The aim of this study was to assess the effects of the T66I and E138K substitutions, alone and in combination with R263K, on viral replicative capacity and resistance to INI.…”
Section: R263k Integrase Mutationmentioning
confidence: 99%
“…The second-generation HIV-1 integrase strand transfer inhibitor (InSTI) dolutegravir (DTG) has had dramatic clinical impact, demonstrating both efficacy (1-5) and a high barrier to resistance (6)(7)(8). Despite the remarkable success of DTG, its pharmacodynamic properties are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%